The effect of crop coverage on the daily dynamism of the soil’s CO2 emission - Szőllősi, Nikolett; Juhász, Csaba; Kovács, Györgyi; Zsembeli, József (Acta Agraria Debreceniensis, 2010)
Nowadays one of main goals of international ecosystem research the measurement of greenhouse gases (CO2, N2O and CH4) in different places. The fluctuation of these greenhouse gases – quantity and trend in the case of CO2 and CH4 – could be diverse with atmosphere because it depends on several effects of factors like climate, soil type, vegetation. In grassland out of the three greenhouse gases which fill a part in gas emission, in the case of CO2 soil and vegetation are the most important factors (Soussana et al., 2007). In the aspect of global carbon balance grasslands are very important by their large area extension, total carbon content, organic content store (10% of the global carbon storage) (Lemmens et al., 2006). In this summer measurements were carried out to determine CO2 emission of the soil from different soil surfaces like grass covered and bare soil surface during a whole day.